1984
DOI: 10.1029/wr020i012p01853
|View full text |Cite
|
Sign up to set email alerts
|

Wetting front advance and freezing of meltwater within a snow cover: 1. Observations in the Canadian Arctic

Abstract: In a naturally stratified snow cover the movement of meltwater into dry snow is complicated by the interaction of the wetting front with stratigraphic horizons. Field observations showed that when the wetting front reached premelt stratigraphic horizons, water ponded at the interface and then flow fingers developed and penetrated the lower stratum. The flux in these fingers, which was increased to about twice that of the surface flux, was used to feed water to the impeding horizons where it froze to form ice l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
186
3
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(200 citation statements)
references
References 30 publications
10
186
3
1
Order By: Relevance
“…The time to warm the entire snowpack was on the order of 2 h, and after the snowpack became isothermal, there was very little variation from 08C. On the basis of these vertical temperature profiles, the estimated travel speed of the warming front is 0. warming of a snowpack is a nonhomogeneous and complex process (Colbeck 1978;Marsh and Woo 1984), our warm-front propagation speed is close to the 0.22 m h 21 propagation speed of meltwater within a snowpack determined by Jordan (1983). During the transition from dry to wet snow, it has been reported that sudden releases of liquid water can occur (Colbeck 1978).…”
Section: February 2014 B U R N S E T a Lsupporting
confidence: 70%
See 1 more Smart Citation
“…The time to warm the entire snowpack was on the order of 2 h, and after the snowpack became isothermal, there was very little variation from 08C. On the basis of these vertical temperature profiles, the estimated travel speed of the warming front is 0. warming of a snowpack is a nonhomogeneous and complex process (Colbeck 1978;Marsh and Woo 1984), our warm-front propagation speed is close to the 0.22 m h 21 propagation speed of meltwater within a snowpack determined by Jordan (1983). During the transition from dry to wet snow, it has been reported that sudden releases of liquid water can occur (Colbeck 1978).…”
Section: February 2014 B U R N S E T a Lsupporting
confidence: 70%
“…In an effort to better understand the meteorological conditions that affect snowmelt, energy budgets of snowpacks have been studied for nearly 80 yr. Many studies use slow-response meteorological instruments with empirical bulk aerodynamic formulas to estimate the turbulent energy fluxes (e.g., Niederdorfer 1933;Sverdrup 1936;Takahashi et al 1956;Schlatter 1972;Male and Granger 1981;Marks and Dozier 1992;Marsh and Pomeroy 1996;Cline 1997;Hood et al 1999;Hawkins and Walton 2007), whereas more recent studies use fast-response instrumentation with the eddy covariance technique to calculate turbulent energy exchange (Hicks and Martin 1972;McKay and Thurtell 1978;Yen 1995;Mahrt and Vickers 2005;Hayashi et al 2005;Molotch et al 2007;Marks et al 2008;Reba et al 2009;Mott et al 2011). Marks et al (2008) showed that, for a snowpack under a pine canopy, the mean differences calculated over several weeks between the eddy covariance and bulkmethod fluxes were within 1-4 W m 22 (with better agreement during the day than at night); hourly differences, however, were significantly larger than the longterm mean difference.…”
Section: Introductionmentioning
confidence: 99%
“…Both snow damming and meltwater percolation delay runoff (Marsh and Woo, 1984;Kane et al, 1991), while local advection hastens melt at the end of the melt period (Neumann and Marsh, 1998). Snow damming is the process by which initial runoff is attenuated by snow deposited in the stream channel.…”
Section: Discussionmentioning
confidence: 99%
“…Once melt occurs, melt water infiltrates through the snowpack and can pond at stratigraphic horizons (e.g., created by snow metamorphism) allowing for the formation of flow fingers. As these infiltrate to the the cold lower layers of the snowpack they can re-freeze, resulting in a major source of latent heat to the snowpack (Marsh and Woo, 1984).…”
Section: Surface Energy Balancementioning
confidence: 99%